Pengaruh Pendidikan Dan Pelatihan Manajemen Terhadap Efektifitas Operasional Usaha Kecil - Sukardi Sukardi; Muhamad Arief Noor; Tohiroh Tohiroh; Siti Mulasih (Jurnal Ilmiah Ekonomi, Manajemen dan Bisnis, 2024)
This study aims to evaluate the effect of management education and training on the effectiveness of small business operations. The objective of this study is to determine whether management education and training can improve the effectiveness of operational effectiveness of small businesses, as well as to identify the most effective method of effective in improving such operational effectiveness. This research will be conducted using survey method and statistical data analysis. Data will be collected through questionnaires distributed to small business owners who have participated in the management education and training program, and to who have participated in management education and training programs, as well as those who have not. who have not participated. Data analysis will be conducted using descriptive and inferential statistical techniques descriptive and inferential statistical techniques to identify the relationship between the variable management education and training with small business operational effectiveness. The results of the study are expected to provide a better understanding of the the importance of management education and training in improving the effectiveness of small business operations. The implication of this study is that small business owners small business owners need to pay attention to investing in management education and training as a strategy to improve their operational performance